Compact six-band coupled-fed planar inverted-F antenna for slim mobile phone - Bharti P.K.; Singh H.S.; Pandey G.K.; Meshram M.K.; Tripathi H. (My University, 2025)
In this paper, the planar inverted-F antenna (PIFA) is proposed for the multi-band mobile phone application. To reduce the size of the antenna, folded and shorted structure is used. The proposed antenna is compact, low-cost and it is appropriate for the GSM900 (890-960 MHz), GPSL1 (1565-1585 MHz), DCS1800 (1710-1880 MHz), DCS1900 (1850-1990 MHz) DECT (1880-1990 MHz), and UMTS2100 (1920-2170 MHz) cellular mobile phone applications. The peak realized gain of an antenna is around 5.5 dBi at GSM900 band and in between 3-4.8dBi for higher operating bands. The return loss, radiation patterns and peak realized gain of the antenna are simulated using Ansoft HFSS and also compared with CST Microwave Studio results. © 2013 IEEE.